«Програмність в українській баянній музиці (1960-2010 роки)» - Тищик, Вадим (My University, 2021)
Дисертацію присвячено програмній музиці – розповсюдженому явищу баянної творчості України (як композиторської, так виконавської). На ґрунті вивчення музикознавчих джерел та творчої практики композиторів-баяністів 1960-2010 років надано дефініції, які cформували уявлення про музичну семантику в контексті академічної творчості для баяну. Програмність в музиці (в широкому сенсі) – це наявність позамузичних чинників в художній концепції твору, що впливають на композиторський задум та його виконавську реалізацію. Програмність у баянному творі на сучасному етапі творчої практики потрактовується як різновид музичної семантики, що втілена композитором іманентно-музичними засобами через вербальне позначення авторського повідомлення для виконавців та слухачів. Надано характеристику програмним творам для дітей (зокрема, В. Власова) на тлі загальних тенденцій розвитку баянного мистецтва. Виявлено стильові закономірності програмних творів крупної форми для баяна з оркестром, обґрунтовано концепції програмності у Другому концерті для баяну з оркестром А. Гайденка, у «Давньокиївських фресках» сюїті-зошит для баяна А. Сташевського, «Слов’янській сонаті» В.Зубицького, а також програмних композицій І. Єргієва як репрезентації новітніх звукообразних форм музикування XXI ст. Зроблено висновок, що програмність як явище композиторсько-виконавської творчості не втратила свого історичного значення для композиторів та виконавців різних поколінь. З точки зору наукового моделювання змісту музики програмність та семантика співвідносяться як загальне та конкретне. The thesis deals with program music as a widespread phenomenon of button accordion art in Ukraine (both composers and performers). Based on studying musicological references and creative practical training of composers- button accordionists of the 1960s-the 2010s, there are definitions which formed the idea of musical semantics in the context of academic art for button accordion. Programming in music (in a broad sense) is non-musical factors in the artistic concept of the piece of music that affect the composer's idea and performance. At the present stage of creative practical training, programming in an button accordion piece is interpreted as a kind of musical semantics, which is embodied by the composer in immanent musical means through verbal design of the author's message for performers and listeners. The types of programming in button accordion art (compositional works and their performance) are substantiated on the basis of generalizing mutual influences of different kinds of arts in genres of academic folk-instrumental music-making: generalized, generalized-plot, sound-imitating, picture-associative, genre-related, genre as intergenre synthesis. The stylistic patterns of big program works in different genres (suites, concerts with a chamber orchestra, etc.) in the aspect of performing the program idea of the composer are analyzed. For example, V. Zubytsky’s accordion sonata № 2 Slovyanska is an example of generalized programming, typical of the romantic era of Ukrainian academic music (from M. Lysenko’s works to B. Lyatoshynsky’s symphony and even “Kyiv avant-garde” representatives). A. Haydenko's button accordion works reflect general foundations of the national revival of Ukrainian art in the 1990s and 2000s. Antiquity as a historical category of the cultural process is a component of modern concepts of music; therefore, his works are a clear manifestation of the trend. The semantics of the musical language of his works is a reflection of the neo-pantheistic worldview. The author consciously points to the archetype of historical antiquity and its mental features in the Ukrainian musical culture, so that performers and listeners can determine and understand the style of the original accordion piece of music. The artistic world of button accordion music faces the history of Ukrainian culture, its national picture of the world through reproducing folk rites, re-intoning Ukrainian thoughts, songs, dances, including - through program titles, author's instructions on rethinking prefolk tales, personal associations with the historical-cultural past of various Slavic peoples. “The Ancient Kiev Frescoes” by A. Stashevsky is a testament to the artistic search and expression of the artist's philosophical and historical thinking and the corresponding techniques of performing skills. "Reincarnation" of any historical, literary, pictorial work in music with determining the degree of correlation the new work to its origin, because it depends on understanding both programming (plot, genre, picture) and the content of interspecies translation, without which true interpretation of the work is impossible. An example of the original embodiment of the program idea is the piece of music "Island of Happiness" (op. 3, № 4) by I. Ierhiev, created for violin, accordion and piano (organ). The appeal to Eastern imagery, firstly, testifies to the semantics of Orientalism in contemporary Ukrainian music, and secondly, determines the principles of compositional-dramaturgical, thematic, textural and timbre organization of this piece of music. It is a manifestation of the individual vision of the "sound image" of the button accordion in the modern world, which is represented in an updated form (according to the author's definition, modern button accordion). The conclusion is reached that programming as a phenomenon of composer-performer art still has its historical value for new generations of accordion players. From the point of view of scientific modeling music content, programming and semantics correlate as general and specific.
Тищик В. Б. «Програмність в українській баянній музиці (1960-2010 роки)» : дис. … канд. мистецтвознавства : 17.00.03 / Тищик Вадим Борисович ; Харківський національний університет мистецтв імені І. П. Котляревського. – Харків, 2021. – 200 с.
Keywords: програмність, музична семантика, баянне мистецтво, дитяча баянна музика, композитори-баяністи України; programming, musical semantics, button accordion art, children’s accordion music, composers-accordionists of Ukraine